Likovnooblikovni razvoj učencev v osnovni šoli - Duh, Matjaž; Korošec, Renata (Revija za elementarno izobraževanje, 2009)
The artistic development of children in primary school. The research presented here deals with the problem of artistic development as it concerns primary school children. This problem is connected to many important criteria within the context of analysis and evaluation of a child's artwork. The research was based on a sample of 11 and 12-year-old pupils. Observing the artistic development of children using the above-mentioned criteria has proven that the values acquired are equally distributed between both genders. During the observation of six individual criteria of artistic development, five of them showed no statistically important differences between boys and girls. This was proven with the use of the t-test. From an analysis of the findings in certain criteria of artistic development, it was also concluded that the results of artistic development are distributed similarly to other skills in heterogeneous groups.